Glioblastoma Distance From the Subventricular Neural Stem Cell Niche Does Not Correlate With Survival - Mistry, Akshitkumar M.; Mummareddy, Nishit; Salwi, Sanjana; Davis, Larry T.; Ihrie, Rebecca A. (Frontiers in Oncology, 2020)
Objective: To determine the relationship between survival with glioblastoma distance from the ventricular-subventricular neural stem cell niche (VSVZ). Methods: 502 pre-operative gadolinium-enhanced, T1-weighted MRIs with glioblastoma retrieved from an institutional dataset (n=252) and The Cancer Imaging Atlas (n=250) were independently reviewed. The shortest distance from the tumor contrast enhancement to the nearest lateral ventricular wall, the location of the VSVZ, was measured (GBM-VSVZDist). The relationship of GBM-VSVZDist with the proportion of glioblastomas at each distance point and overall survival was explored with a Pearson’s correlation and Cox regression model, respectively, adjusting for the well-established glioblastoma prognosticators. Results: 244/502 glioblastomas had VSVZ contact. The proportion of non-VSVZ-contacting glioblastomas correlated inversely with GBM-VSVZDist (partial Pearson’s correlation adjusted for tumor volume R=-0.79, p=7.11x10-7). A fit of the Cox regression model adjusted for age at diagnosis, Karnofsky performance status score, post-operative treatment with temozolomide and/or radiotherapy, IDH1/2 mutation status, MGMT promoter methylation status, tumor volume, and extent of resection demonstrated a significantly decreased overall survival only when glioblastoma contacted the VSVZ. Overall survival did not correlate with GBM-VSVZDist. Conclusions: In the two independent cohorts analyzed, glioblastomas at diagnosis were found in close proximity or in contact with the VSVZ with a proportion that decreased linearly with GBM-VSVZDist. Patient survival was only influenced by the presence or absence of a gadolinium-enhanced glioblastoma contact with the VSVZ. These results may guide analyses to test differential effectiveness of VSVZ radiation in VSVZ-contacting and non-contacting glioblastomas and/or inform patient selection criteria in clinical trials of glioblastoma radiation.